Visitor's perception of Berjaya Times Square Theme Park - Buang, Nazrul Ashraff (2016)
Theme parks are interesting segments of the tourism market. In today’s competitive environment of modern tourism research, only few studies have explored the service quality of theme park and its huge potential for tourism development and industry. This main objective of this study to investigate the visitor’s perception of the service quality at Berjaya Times Square Theme Park. The study was conducted using 25 characteristics face to face interview to finish the questionnaire based on Modified THEMEQUAL model. Total number of respondents are 150. The data was analysed using descriptive and multiple regression analysis. The results stated that all 25 characteristics achieved high scores indicating that the theme park give a good perception of service quality to the visitors. A multiple regression analysis identified the dimension “reliability”, “assurance” and “empathy” as best predictors of visitor’s satisfactory level there. The paper contributes to the existing literature of service quality in the context of theme park. This study and research can be used both by managers in theme parks for improving service quality as well as the scientific community as an encouragement for further studies and researches.